ANALISIS TEORI MUKHOTTIAH DAN MUSHOWWIBAH KAJIAN KRITIS TERHADAP DINAMIKA PENETAPAN HUKUM ISLAM KONTEMPORER - Akbar, Ahmad Rozai (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2024)
This research aims to analyze the Mukhottiah and Mushowwibah theories in the context of contemporary Islamic law, focusing on their ability to respond to the dynamics of the times. Mukhottiah theory, which emphasizes a single truth, provides legal stability, while Mushowwibah theory offers flexibility that is responsive to social and economic changes. This research uses a library research method with a descriptive-critical qualitative approach, which utilizes relevant literature to evaluate the principles and application of both theories. The results show that Mukhottiah is suitable for laws that require certainty, while Mushowwibah is relevant in modern issues that require context adaptation. These two theories, when applied in balance, allow Islamic law to remain stable and relevant, making it a guideline capable of effectively addressing contemporary challenges for Muslims in various contexts.